PAHAM KETUHANAN DALAM TRADISI GUMBREGAN DI DUSUN GESING, KECAMATAN TANJUNGSARI, WONOSARI, GUNUNGKIDUL - Triyono, Yohanes; Debritta P.W, Oktavianus; Widodo, Agus (STP St. Bonaventura Medan, 2024)
The Gumbregan tradition is a local cultural heritage that is still highly revered in several areas in Gunungkidul, particularly in the Tanjungsari District. This tradition is not just a series of rituals or cultural practices, but also reflects a profound understanding of the relationship between humans and God, as well as the role of nature in daily life. This paper aims to analyze the concept of divinity in the Gumbregan Tradition in more detail. The understanding of the nature and role of God in this tradition is the main focus of the research. Through a qualitative approach combining data from various previous studies, this article presents an in-depth analysis of how the people of Gunungkidul understand and practice the Gumbregan Tradition as a manifestation of their belief in and respect for God. The findings of this article are expected to provide a better understanding of the Gumbregan Tradition and its social and religious implications in the context of the local community.